اثر تقانة المعلومات في عمليات إدارة المعرفة: دراسة ميدانية في عينة من الشركات الصناعية في محافظة نينوى - د. أكرم احمد الطويل; د.حكمت رشيد (PROSPECTIVE RESEARCHES, 2005)
The present research deals with both information technology and knowledge Operations Management in a comprehensive frame by building a cultural and field frame to determine the effect of the information technology in the operations of knowledge management on a sample of industrial companies in Nineveh Governorate. In general, the research tries to answer the following questions: 1-Has the company’s under study, the understanding about the concept and significance of information technologies? 2-Is there an obvious perceptive about knowledge operations management for the companies management’s under study? 3-What is the nature and kind of correlation and the effect between information technology and knowledge management in the studied companies? The research has came out of a set of conclusions such as: 1-There is a relative correlation and a significant effect between information technology and knowledge management operations in the companies under study? 2-The results of analysis that are illustrated in all the knowledge management Operations dose not get its efficiency from software, as in the equipment’s and tools , dose not contribute positively in both knowledge identification and determining its objectives. Based on the conclusions reach by the research, a number of recommendations were set forth.